Filtration formulas for solutions of nonlinear equations with random right-hand sides - Sokhadze, G. A. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
Explicit filtration formulas are obtained for the solutions of nonlinear differential equations with random right-hand sides. In the case of a Gaussian random process, these formulas are simplified.